2021
DOI: 10.1038/s41598-021-98146-x
|View full text |Cite
|
Sign up to set email alerts
|

Action video game training improves text reading accuracy, rate and comprehension in children with dyslexia: a randomized controlled trial

Abstract: Dynamic visual attention training using Action Video Games (AVGs) is a promising intervention for dyslexia. This study investigated the efficacy of 5 h (10 × 30 min) of AVG training in dyslexic children (aged 8–13) using ‘Fruit Ninja’, while exploring whether increasing attentional and eye movement demands enhanced AVG effectiveness. Regular (AVG-R; n = 22) and enhanced AVG training (AVG+; n = 23) were compared to a treatment-as-usual comparison group (n = 19) on reading, rapid naming, eye movements and visuo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Importantly, the structural connectivity networks associated with different aspects of skilled reading showed that interconnectivity between left hemisphere language and right hemisphere attentional areas underlies both lexical and sublexical reading 12 . Moreover, both training 26 , 33 , 34 , 36 , 37 41 ; see 43 for a recent review) and longitudinal 26 , 28 , 29 , 33 , 34 , 59 studies have previously demonstrated the causal links between visuo-attentional deficits and RD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the structural connectivity networks associated with different aspects of skilled reading showed that interconnectivity between left hemisphere language and right hemisphere attentional areas underlies both lexical and sublexical reading 12 . Moreover, both training 26 , 33 , 34 , 36 , 37 41 ; see 43 for a recent review) and longitudinal 26 , 28 , 29 , 33 , 34 , 59 studies have previously demonstrated the causal links between visuo-attentional deficits and RD.…”
Section: Discussionmentioning
confidence: 99%
“…Since visuo-spatial attention is relevant for reading acquisition, and it is frequently dysfunctional in children with RD, its clinical evaluation is crucial for the correct identification of a specific training designed to improve RD in neurodevelopmental disorders. Considering that different visuo-spatial attention interventions can improve reading skills in children with RD 34 , 36 , 38 , 39 , 41 , 74 77 , see 43 for a review), an efficient reading remediation program should integrate auditory-phonological and visuo-attentional interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Some emerging studies have provided some support for the efficacy and potential of eye-tracking-based training as a cognitive intervention 26 40 . In particular, studies reported positive effects on improving attention, memory and executive functions in post-stroke patients 29 , 30 , significant improvement in attention and impulsivity in children with ADHD 26 , 28 , improvement in reading 31 , 38 , comprehension 31 , executive function 40 , visual attention and verbal memory 39 in children with dyslexia, reduction in repetitive behaviors 35 , and improvement in visual sustained attention 33 and emotion recognition 36 in children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…As the conventional remediation class teaches Chinese reading and writing skills, it is hypothesized that children receiving conventional training will demonstrate improvement in reading abilities, but may not in learning and memory. Although the eye-tracking training would not teach reading skills as the remediation class, it is hypothesized that the children in the Eye-tracking Training group will show as much improvement in the reading skills as the conventional class given that eye-tracking training has been shown to improve reading abilities in children with SEN 31 , 37 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Various studies using Wii-based, or computer, games have shown that a short and intensive treatment with an action-based video game, rather than the training of phonological or orthographic skills, may improve reading abilities in dyslexic children, specifically visual-attention abilities, spatial cognition, auditory spatial attention, and response time speed [ 25 , 26 , 27 , 28 , 29 ]. A recent study using VR technology for the rehabilitation of reading deficits in dyslexia found that a virtual environment may represent a valid approach to improve attentional skills [ 16 ].…”
Section: Introductionmentioning
confidence: 99%